Efficient Non‐Fullerene Organic Solar Cells Based on a Wide‐Bandgap Polymer Donor Containing an Alkylthiophenyl‐Substituted Benzodithiophene Moiety. Issue 20 (10th July 2019) - Xie, Ruihao; Ying, Lei; An, Kang; Zhong, Wenkai; Yin, Qingwu; Liao, Shengzu; Huang, Fei; Cao, Yong
Abstract: Two wide‐bandgap polymer donors containing an alkylthiophenyl substituted benzo[1, 2‐ b : 4, 5‐ b′ ]dithiophene moiety, namely PTZPO and PTZPS, were designed and synthesized. Both polymers exhibit relatively wide optical bandgap of 1.95 V with similar absorption profiles. The polymer PTZPS with alkylthiophenyl substituted benzo[1, 2‐ b : 4, 5‐ b′ ]dithiophene units showed enhanced light‐harvesting capabilities, leading to improved short‐circuit current densities. The PTZPS : ITIC film shows more appreciable film morphology and phase separation than the film composed of a blend of ITIC with alkoxyl substitutions containing copolymer PTZPO, which facilitates exciton dissociation and charge transport. The PTZPS : ITIC‐based non‐fullerene organic solar cells show clearly improved short‐circuit current density and an impressively high power conversion efficiency of more than 11 %. These observations demonstrate the great promise of using PTZPS as electron‐donating materials for high‐performance non‐fullerene organic solar cells. Abstract : Efficient solar cells : Two wide‐bandgap polymer donors containing an alkylthiophenyl substituted benzo[1, 2‐ b : 4, 5‐ b′ ]dithiophene moiety (denoted as PTZPS and PTZPO) were designed and synthesized. The non‐fullerene organic solar cells based on PTZPS : ITIC exhibited clearly improved short‐circuit current density and an impressively high power conversion efficiency over 11 %. These observations demonstrate the great promise of using PTZPS as electron‐donating materials for high‐performance non‐fullerene organic solar cells.